FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN PENERIMAAN UNQUALIFIED OPINION WITH MODIFIED PARAGRAPH GOING CONCERN - YUNITA YUNITA; DEASY ARIYANTI RAHAYUNINGSIH (Media Bisnis, 2013)
The purpose of this study is to investigate empirically the relationship between audit quality, company’s financial condition, prior audit opinion, company’s growth, company’s size, and debt default that influence the company’s acceptance of unqualified opinion with modified paragraph going concern. Data to be used is secondary data and were taken from Indonesia Stock Exchange official website. The research used 42 non-financial companies as sample by using purposive sampling method. This study used logistic regression to test the hypothesis. Data for this study comprises from the financial statement of non-financial companies in Indonesia over four year period of 2008-2011. The research finding can be summarized as follows. The result showed that the prior audit opinion has significant influence over unqualified opinion with modified paragraph going concern. On the other hand, audit quality, company’s financial condition, company’s growth, company’s size, and debt default don’t have influence on unqualified opinion with modified paragraph going concern.